Convergence or divergence of continuing vocational training in Europe? Empirical findings and theoretical conclusions for adult education - Bernd Kapplinger (Adult Education Research Conference, 2011)
The paper describes trends of convergence and divergence in enterprise-provided continuing vocational training in Europe between 1999 and 2005. Based on the survey CVTS, the indicators for courses incidence, access, intensity, direct costs and the indicator learning at the workplace will be analyzed. The paper concludes with an outlook with references to sketches of an educational theory to be written for this field of adult education.
Keywords: Vocational training; enterprises; enterprise survey; Europe